Enhanced antioxidant phytochemicals and catalase activity of celery by-products by a combined strategy of selenium and PGPB under restricted N supply - Collado-González, Jacinta; Piñero, María Carmen; Otálora, Ginés; López-Marín, Josefa; del Amor, Francisco M. (Frontiers in Plant Science, 2024)
Introduction The reduction of N supplied combined with the use of biostimulants can be an efficient strategy that allows sustainable agriculture to achieve better economic, nutritional and environmental goals without reducing production. Moreover, the industrial processing of celery generates large amounts of waste. Therefore the purpose of this study was improve crop management strategies to reduce nitrate pollution while turning crop waste into value-added products for others sectors. Methods Consequently, in this work twelve treatments were examined: three N nitrogen content in the nutrient solution (100% control, 60%, and 30%) combined with the inoculation of the roots with Azotobacter salinestris, and foliar application selenium solution (8 μM, Na2SeO4). The celery parts from plants grown under limited N dose showed a higher antioxidant activity and TPC (total phenolic compounds) content. Results and discussion The antioxidant activity increased 28% in leaves and 41% in by-products and TPC improved 27% in leaves and 191% in by-products respect to the control. Besides, a significant reduction of β-carotene content (56%, 11% and 43% in petioles, leaves and by-products respect to the control, respectively) was obtained in plants fed with restricted dose of N. The catalase activity was not affected by N dose. The inoculation of the plants with Azotobacter, together with a reduced N dose, achieved a greater accumulation of all the parameters studied. This accumulation was maximum when Se was applied to the leaves compared with the control and depending on the celery part: TPC (121-450%); antioxidant activity (60-68%), of catalase activity (59% - 158%), and of pigments content (50-90%). These findings can boost the valorization of celery by-products as excellent source of bioactive compounds.